Evaluation of Lactobacillus reuteri DSM17938 as starter in cheese production - Karlsson, Madeleine (2013)
The probiotic bacteria Lactobacillus reuteri DSM17938 was evaluated as a starter culture in cheese production, with the intention to produce a new interesting product within the functional food market. Growth and acidification rate in milk subjected to different heat treatments, as well as supplementation with growth promoting factors or support cultures was measured during controlled fermentations. The results showed that the weak proteolytic activity of L. reuteri could be compensated for by supplementation with 1% casamino acids or 5% MRS broth. Furthermore, a decrease in growth and acidification rate could be seen when using yoghurt culture or Lactobacillus delbrueckii as adjunct cultures. L. reuteri DSM 17938 was successfully incorporated into a fresh cheese with high viability during the storage period, suggesting that fresh cheese is an excellent carrier for the bacteria. The inhibitory activity of L. reuteri on a non-pathogenic mutant of Escherichia coli O157:H7 (EHEC) and Staphylococcus aureus was also tested. Both pathogens were inhibited in cheese with L. reuteri and the control, opening for further investigations in the field. A limited population of L. reuteri DSM 17938 was also successful incorporated in a hard cheese produced at Skogsbackens dairy. However, the survival was excellent during the storage period of 83 days, suggesting that the cheese could be a good carrier for L. reuteri.